The role of renewable energy in mitigating carbon emissions: Insights from China's energy consumption patterns - Muhammad Sohaib; Abdul Majeed; Jingru Liu; Judit Oláh (Energy Strategy Reviews)
China's rapid economic growth has made it the world's largest carbon emitter, creating urgent environmental challenges that require immediate attention. As urbanization advances, so does the energy demand, with a large proportion of that energy being provided by fossil fuels, which has further escalated carbon emissions. The resulting increase in carbon emissions poses a serious threat to global climate stability and requires immediate action to mitigate its impact on the environment. The urge to reduce environmental effects has called for solutions, such as a shift to renewable energy. Thus, this study aims to establish the relationship between renewable energy consumption, economic growth, fossil fuel use, urbanization, industrialization, and carbon emissions in China from 1990 to 2022. We explore these variables using Autoregressive Distributed Lag (ARDL) and nonlinear symmetrical estimation methods. These findings suggest that carbon emissions are positively linked to fossil fuel use, economic growth, urbanization, and industrialization, indicating that these determinants play a significant role in environmental degradation. Conversely, renewable energy reduces carbon emissions and contributes to environmental sustainability. It confirms the need to improve renewable energy integration and increase awareness of China's severe environmental concerns, which are exacerbated by its economic and industrial development. This study offers critical insights for Chinese policymakers by analyzing data from 1990 to 2022 to quantify the extent to which the adoption of renewable energy can offset emissions resulting from economic growth, fossil fuel use, urbanization, and industrialization. Our findings provide China-specific evidence to support its emission reduction targets and contribute globally relevant methods for sustainable development planning. The quantified relationships provide a framework for evaluating the effectiveness of policies in transitioning to low-carbon growth.